Enhanced recovery after surgery in urology - Kermode, Andrew; Jones, Chris (Digestive Medicine Research, 2019)
Major urologic surgery has an association with frequent morbidity and protracted inpatient admissions, especially prolonged surgery such as radical cystectomy (RC). Enhanced recovery after surgery (ERAS) principles originally developed for colorectal surgery have demonstrated reduced surgical stress leading to improved postoperative recovery and reduced length of stay (LOS). This has led to ERAS protocols being adopted across surgical specialities, including urology. ERAS guidelines for urology published in 2013 have since led to extensive research in the implementation of these principles into practice, alongside comparative research into individual ERAS principles such as minimally invasive surgery. Through this review we will demonstrate current evidence and recommendations with consideration of the preoperative, intraoperative and postoperative care, noting areas where evidence is lacking or requires further exploration. We will explore the developments to the implementation of ERAS principles in current practice, including the use of alvimopan to decrease time to first bowel function, the changing role of regional anaesthesia (including the use of locoregional blocks), and the increasing use of minimally invasive surgical technique (e.g., robot assisted RC) leading to overall improved patient care and reduced LOS.